DNA demystified : unraveling the double helix - McHughen, Alan (New York : Oxford University Press, 2020)
""If you're mystified by DNA and genetics, relax. Settle into a comfy chair as we explain what DNA is and how it works its apparent magic, revealing it's not so magical after all. We'll also cover chromosomes, genes and genomics, and how they impact our daily lives. These initial pages provide a quick overview of some common questions folks have about DNA: what it is, what you should know about it, where it comes from. If it seems like we're glossing over your favorite topic, be patient, as we'll explore these and many other topics in greater depth in the subsequent chapters. For now, settle in! It's time to unpack some mysteries and explode some myths, while still marveling at the awesome star power of DNA. Like all celebrities, DNA carries a mystique, a compelling story combining remarkable skills with some manufactured hype. 'It's in our DNA' is now a standard refrain for marketers and individuals trumpeting some essential virtue: honesty, courage, integrity, permanence, the spirit of discovery1. The aura of DNA sells everything from colleges and companies to cars, electric fences, and even literary agents. The marketing hype is often misplaced, but DNA is undoubtedly a wondrous molecule. It's the only known molecule capable of reproducing itself, and is present in all living things. DNA is, indeed, the essence of life itself. Between the Presidential citations, popular television shows such as CSI (Crime Scene Investigation) and a multitude of gratuitous marketing clichés, almost everyone knows "DNA". Or, at least, they think they know about DeoxyriboNucleic Acid, aka "DNA". The New York Times index shows over 500 news articles on DNA in the first half of 2019 alone, an average of over two stories per day.2 Yet many otherwise well-informed readers don't know what DNA is or how it works.""--
Includes bibliographical references and index.
Keywords: DNA; Forensic genetics